1993
DOI: 10.1099/00221287-139-5-949
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the trypsin-like enzymes of Porphyromonas gingivalis W83 using a radiolabeled active-site-directed inhibitor

Abstract: The trypsin-like enzyme activity of Porphyromonas gingivalis is an important virulence determinant of this organism in destructive periodontitis. An active-site-directed inhibitor, tyrosyl-alanyl-lysyl-arginine chloromethyl ketone (YAKR-CK) was radio-iodinated and used with SDS-PAGE and autoradiography to determine the number and molecular masses of enzymes with trypsin-like specificity produced by P. gingivalis W83. Two forms (I & 11) were detected in both crude culture supernatant and whole cell sonicates. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 40 publications
2
33
0
Order By: Relevance
“…55,56 To show that the measure of aggregation observed (increase in the light transmittance level) was reflective of true platelet activation and is thus genuine aggregation, rather than an agglutination phenomenon, an inhibitor of platelet activation was used. Preincubation of platelets with 100 ng/mL PGI 2 or 10 M forskolin (inhibitors of platelet activation) at 37°C for 15 minutes completely inhibited the aggregation induced by 0.25 nM HRgpA and 20 nM RgpB (data not shown), verifying that HRgpA and RgpB indeed cause true platelet aggregation.…”
Section: Hrgpa and Rgpb Induce Platelet Aggregationmentioning
confidence: 99%
“…55,56 To show that the measure of aggregation observed (increase in the light transmittance level) was reflective of true platelet activation and is thus genuine aggregation, rather than an agglutination phenomenon, an inhibitor of platelet activation was used. Preincubation of platelets with 100 ng/mL PGI 2 or 10 M forskolin (inhibitors of platelet activation) at 37°C for 15 minutes completely inhibited the aggregation induced by 0.25 nM HRgpA and 20 nM RgpB (data not shown), verifying that HRgpA and RgpB indeed cause true platelet aggregation.…”
Section: Hrgpa and Rgpb Induce Platelet Aggregationmentioning
confidence: 99%
“…However, because MAb 5A1 does not block Hb binding (N. Hunter, unpublished data), there is no evidence to indicate that the epitope shared by HA2 and HA1 is involved in Hb or Hm binding. It has been proposed HA1 functions for hemagglutination (11). From these assays it is concluded that HA2-proteins are major contributors to cell surface Hb binding.…”
Section: Neutralization Of Hb Bindingmentioning
confidence: 99%
“…gingivalis possesses a number of factors of potential importance in the periodontal disease process. Among these factors are fimbriae (19,24,38,63,66), lipopolysaccharide (20), hemagglutinins (11,34,40,44,45), capsule (55,61), and proteases (1,9,42,43,59). The proteolytic capability of P. gingivalis strains is known; however, only recently have protease genes been cloned.…”
mentioning
confidence: 99%